The Arab Poetic Self in Other Languages A Study of the part of Contemporary Maghreb Poetry in Translation: الأنا الشعري العربي في لغات الآخر دراسة في نصيب الشعر المغاربي المعاصر من الترجمة - Oughlici , youcef (Maalim, 2026)
This article aims to trace the relationship between the Arab poetic self and the linguistic other by examining translations of poetry from the Arab Maghreb into various languages of the world, starting from the problem of poetic translation itself and moving through the actual translations produced and the challenges they entail. It employs a methodology that analyzes the problematic into its major components and describes the achievements in each component, drawing on history to place the problematic within its appropriate interpretive framework. The article drew important conclusions regarding the nature of the languages of the ‘other’ that were most attractive to this poetic self, the identities of the poets who benefited most from this practice, and the conditions of increasing dynamism in this specific field of translation.